PERLINDUNGAN KONSUMEN TERHADAP PELAKU USAHA ROTI KEMASAN YANG TIDAK MEMPUNYAI LABEL KADALUARSA DI KOTA PEKANBARU - Ramelan Nazara; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Rapid economic development has resulted in various types and variations of goods and / or services. The marking or labeling is intended so that consumers get correct information about the product. Because the right choice of consumer choice regarding the goods or services needed depends on the truth and responsibility of the information provided by the parties concerned. The need for a product equipped with information is one of the efforts towards consumer protection. Because with that information, consumers can find out the usefulness and from what ingredients the product was made. Provision of information about this product can be carried out by packaged food product traders by providing information on the date, month, and year of expiration on the product packaging in question.The problem that the author makes the basis of this research is how the responsibility of business people for packaged bread that does not have an expired label in the city of Pekanbaru and how the legal certainty of selling packaged bread that does not have an expired label in the city of Pekanbaru. The purpose of this study is to determine the responsibility of packaged bread business actors who do not have an expired label in the city of Pekanbaru and to determine the legal consequences of packaged bread sellers who do not have expired labels in the city of Pekanbaru.This type of research can be classified into empirical or sociological research types, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in Pekanbaru City and the One Stop Investment Office, data sources used were: primary and secondary data, data collection techniques in this study with observation, interviews and literature review. The results of this study are first. The researcher concludes that most business actors found carrying out food products that do not meet administrative requirements are only given a warning and a prohibition to temporarily circulate and orders to withdraw food products from circulation as stated in Government Regulation No.69 of 1999 concerning Food Labels and Advertisements , if they still do not comply or are found to be still circulating food products whose label requirements are still incomplete, then production permit revocation is granted.Secondly, the Food and Drug Supervisory Agency is only following up on food products that violate the label, mostly in the form of warnings, so that it does not deter businesses from always violating the label, by not listing BPOM numbers and not registering their products with BPOM, thus BBPOM only provides a form of reprimand, and for products that have been sold by threatening the safety of consumers such as products that have expired, are given criminal sanctions listed in Article 62 paragraph 1 of Law No. 8 of 1999 concerning Consumer Protection.Keywords: Expiration, Food, Labe